Integrasi Game Puzzle Budaya dan Model PBL-GBL untuk Meningkatkan Pemahaman Budaya Peserta Didik Sekolah Dasar dalam Pembelajaran IPAS - Bako, Enggi Nurunnisya; Nasution, Ismail Saleh; Sagala, Friska Herawaty (Medan Resource Center, 2025)
This classroom action research investigates how integrating a culturally responsive educational puzzle, GAPURA (Game Puzzle Keragaman Budaya), into Problem-Based Learning (PBL) and Game-Based Learning (GBL) models can enhance students’ understanding of cultural diversity. The study, conducted over two cycles with 21 fifth-grade students at UPT SDN 060858 Medan Tembung, responds to the observed lack of student engagement and low achievement in understanding cultural themes in IPAS learning. Data were obtained through student learning outcome tests, classroom observations, reflections, and documentation. Results revealed a notable improvement in students’ comprehension, with average scores rising from 55.24 in Cycle I to 80.00 in Cycle II, and mastery learning achievement reaching 90.95%. The integration of GAPURA encouraged active participation, empathy, and cooperative learning within a joyful, relevant learning environment. This study concludes that the incorporation of PBL and GBL models with localized, culturally grounded media effectively fosters both cognitive and affective dimensions of cultural literacy, contributing to more meaningful and inclusive IPAS instruction.